Affixes of Minangkabau Language in The Origin and Rantau Area: Study of Morphological Variation - Noviatri Noviatri; Reniwati Reniwati; Gusti Asnan (Masyarakat Linguistik Indonesia Universitas Andalas, 2017)
The article aims to examine the similarities and differences between Minangkabau languages in the origin regions 50 Kota and Pasaman West Sumatra compared to rantau areas Kampar and Rokan Hulu Riau. The study is done by dialectology approach which focuses on affixes. The data are collected by using conversational observation method along with the interview and record techniques. The data are analyzed by using identity method along with immediate constituent analysis and advanced techniques, comparative and contrastive techniques. The result shows there similarities and differences of Minangkabau affixes between both areas.